一种新型、浓度可控的透明质酸生物材料及其制备方法和应用 (2024)
本发明提供了一种新型、浓度可控的透明质酸生物材料及其制备方法和应用，属于生物材料治疗与再生医学技术领域。本发明以透明质酸为主体分子，以胰岛素样生长因子C结构域多肽为客体分子，分别制备金刚烷修饰的胰岛素样生长因子C结构域多肽和β-环糊精修饰的透明质酸，然后将二者通过非共价结合的主客体化学反应制成一种新型、浓度可控的透明质酸生物材料。该透明质酸生物材料具有透明质酸的物理和化学性质，同时又可以结合胰岛素样生长因子C结构域多肽，可以携带任意浓度的该多肽，进而发挥两者的生物活性；该透明质酸生物材料具有可直接结肠内注射和调节肠道功能的作用，从而能够有效促进结肠炎的损伤修复。 The invention provides a novel concentration-controllable hyaluronic acid biological material as well as a preparation method and application thereof, and belongs to the technical field of biological material treatment and regenerative medicine. The preparation method comprises the following steps: by taking hyaluronic acid as a host molecule and insulin-like growth factor C structural domain polypeptide as a guest molecule, respectively preparing adamantane modified insulin-like growth factor C structural domain polypeptide and beta-cyclodextrin modified hyaluronic acid; then the hyaluronic acid and the hyaluronic acid are subjected to a non-covalently bound subject-object chemical reaction to prepare a novel concentration-contr